Analisis Bahasa Daerah Terhadap Penggunaan Bahasa Indonesia Pada Siswa Sekolah Dasar - Aniyati; Silvina Noviyanti; Nazurty; Ratih Aulia Rahma; Khoirun Najwa Awalia; Putri Lestari; Rinda (STKIP Subang, 2026)
This study examines the influence of regional languages on the use of Indonesian among elementary school students. The background of this research is the strong dominance of regional languages as students’ first language, which often affects their use of Indonesian as a second language in formal learning contexts. This study aims to analyze the forms of interference and identify the factors influencing students’ language use. The research employs a qualitative descriptive approach using a literature study method, which involves analyzing and synthesizing relevant sources such as journals, books, and official documents. The findings indicate that regional languages significantly affect students’ Indonesian usage in several linguistic aspects, including phonology, morphology, syntax, and vocabulary. Common forms of interference include code-mixing, inaccurate sentence structures, and pronunciation influenced by regional accents. However, regional languages also play a positive role as a bridge in understanding learning materials, especially at the early stages of education. Therefore, balanced language management is needed in the learning process. Teachers play a crucial role in guiding students to use Indonesian properly while still appreciating their regional language as part of cultural identity. This study highlights the importance of contextual and bilingual learning strategies to support students’ language development effectively.